1997
DOI: 10.1086/304538
|View full text |Cite
|
Sign up to set email alerts
|

Multiwavelength Monitoring of the BL Lacertae Object PKS 2155−304 in 1994 May. I. The Ground‐based Campaign

Abstract: Optical, near-infrared, and radio observations of the BL Lac object PKS 2155[304 were obtained simultaneously with a continuous UV/EUV/X-ray monitoring campaign in 1994 May. Further optical observations were gathered throughout most of 1994. The radio, millimeter, and near-infrared data show no strong correlations with the higher energies. The optical light curves exhibit Ñickering of 0.2È0.3 mag on timescales of 1È2 days, superposed on longer timescale variations. Rapid variations of D0.01 mag minute~1, if re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…For the uncertainties on the data points, see Table 2. (Brindle et al 1986 ;Mead et al 1990 ;Smith & Sitko 1991 ;Smith et al 1992 ;Allen et al 1993 ;Jannuzi et al 1993b ;Courvoisier et al 1995 ;Pesce et al 1997). be wavelength dependent because its spectrum should be signiÐcantly redder than that of the nucleus. In fact, given the measured magnitudes of the host galaxy (M H \ [26.8 ;Kotilainen, Falomo, & Scarpa 1998 and M I \ [24.2 ;Falomo et al 1991), using the color indices of a typical elliptical galaxy reported by Fukugita, Shimasaku, & Ichikawa (1995), Kotilainen et al (1998), andBertone et al (2000), we calculated the host galaxy Ñux in the F host UBV RI bands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the uncertainties on the data points, see Table 2. (Brindle et al 1986 ;Mead et al 1990 ;Smith & Sitko 1991 ;Smith et al 1992 ;Allen et al 1993 ;Jannuzi et al 1993b ;Courvoisier et al 1995 ;Pesce et al 1997). be wavelength dependent because its spectrum should be signiÐcantly redder than that of the nucleus. In fact, given the measured magnitudes of the host galaxy (M H \ [26.8 ;Kotilainen, Falomo, & Scarpa 1998 and M I \ [24.2 ;Falomo et al 1991), using the color indices of a typical elliptical galaxy reported by Fukugita, Shimasaku, & Ichikawa (1995), Kotilainen et al (1998), andBertone et al (2000), we calculated the host galaxy Ñux in the F host UBV RI bands.…”
Section: Discussionmentioning
confidence: 99%
“…The BL Lac object PKS 2155[304 is a nearby blazar (z \ 0.116 ; see Falomo, Pesce, & Treves 1993), one of the brightest at optical to X-ray frequencies, and its polarized optical light has been observed over many years by Brindle et al (1986), Mead et al (1990), Smith & Sitko (1991), Smith et al (1992), Allen et al (1993), Jannuzi et al (1993b), Cour-voisier et al (1995), and Pesce et al (1997). The main results are a polarization fraction P varying from 2% to 10%, a position angle P.A.…”
Section: Introductionmentioning
confidence: 99%
“…(1) Griffiths et al (1979); (2) Griffiths et al (1979), (3) Miller & McAlister (1983), (4) Brindle et al (1986), (5) Hamuy & Maza (1987), (6) Pica et al (1988), (7) Treves et al (1989), (8) Mead et al (1990), (9) Smith & Sitko (1991), (10) Carini & Miller (1992), (11) Smith et al (1992), (12) Jannuzi et al (1993) and (13) Urry et al (1993) as collected in Zhang & Xie (1996); (14) Campbell (2004), (15) Courvoisier et al (1995) and (16) Pesce et al (1997) as collected in Osterman et al (2007); (17) Tommasi et al (2001). Table 1 shows statistics of the data on PKS 2155-304.…”
Section: Summary Of Observationsmentioning
confidence: 99%
“…Several papers estimated or limited central black hole masses using indirect methods, including the shape of the big blue bump in the continuous spectrum (Wang & Zhou 1996), timescale of variability (Pesce et al 1997 and two following papers), rising central rotation curves (Keneko et al 1997), total luminosities (Di Matteo & Fabian 1997), velocity profiles (van den Bosch & de Zeeuw 1996), line asymmetries (Nandra et al 1997), and polarization (Lee & Blandford 1997). Possibly these tell us more about the opinion of the authors than about the galactic centers in question, but also that said opinion is overwhelmingly pro-black hole.…”
Section: Galaxies With Central Black Holesmentioning
confidence: 99%